Black Words and White Space: How Cheryl Foggo’s Pourin’ Down Rain Claims a New Understanding of the Canadian West - Costello, Tara (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
This essay analyzes how Cheryl Foggo’s memoir Pourin’ Down Rain contextualizes itself in the recovery of Black space, identity, and story in Canada. An understanding of Black storytelling, founded in Joanne Braxton’s Black Women Writing Autobiography, provides insight into the ways in which Foggo’s memoir fits within a Black storytelling tradition, and how these forms work to disrupt the kind of tradition preserving the ideological space of the “White West.” An analysis of photography and oral storytelling helps explore how Foggo uses alternative narrative techniques to tell a story that challenges dominant perceptions of Blackness and what historical archiving should look like. Finally, this essay deconstructs perceptions of the Canadian West as established by the region’s pre-existing literary canon, and explores how Pourin’ Down Rain opposes these perceptions by challenging some of the common conventions in White prairie narratives.